A Semantic Study Of The Arabic Word Fitnah In The Quran/ دراسة دلالية العربية لكلمة الفتنة في القرآن - Ikhsan, Arief Maulana; Yusuf, Multazam; Ifawati, Nur Ila; Firdaus, Franky Leo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to determine the meaning of